Impact of Human Waste Management on the estimation of Ancient Maya Population - Wong, Alfred (Estudios de cultura maya, 2018)
The population of ancient Maya has been estimated traditionally by multiplying the number of discovered household mounds and the assumed number of persons per household in a given transect of an archaeological site. This approach is foundationally weak as both key parameters are subject to wide variations over the time course of several centuries. The ubiquitous outcome of this approach is that ancient Maya is nearly always construed to have a very large population base, especially during the Classic period. What is largely omitted in prior studies is the proof of sustainability of such calculated population size in commensuration with, among other things, effective management of human wastes. The waste disposal situation in ancient Tikal is aggravated by the generally flat terrain and the lack of natural drainage channels. The only means of waste disposal would have been by manual labourers conveying the wastes collected daily to dump in cesspools at some distance from high-density human settlements. There was a notable absence of draft animals and wheeled machines including transport vehicles, which could have facilitated such means of waste disposal. The problematic issue of human waste management would certainly have limited the practical size of population cluster in ancient Tikal.